2008
DOI: 10.3168/jds.2007-0838
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium-Naloxone Treatment on Blood Calcium, β-Endorphin, and Acetylcholine in Milk Fever

Abstract: Milk fever is a postpartum syndrome of cows characterized by acute hypocalcemia, which reduces the release of acetylcholine (ACH), inducing flaccid paralysis and recumbency. Our aim was to evaluate the effect of calcium (Ca2+) combined with naloxone (Nx, an opioid antagonist; Ca2+-Nx) on plasma concentrations of ACH, beta-endorphin (betaE), and Ca2+ just before treatment (T0) and at 15, 30, and 90 min after treatment (T15, T30, and T90, respectively). Thirty cows were divided into 3 groups of 10 cows each. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Colostrum contains approximately four times more calcium than normal milk (Anderson et al 2007 ; Tsioulpas, Grandison & Lewis 2007 ). Such sudden drainage of large amounts of calcium into milk can overwhelm the cow’s homeostatic mechanisms (Rizzo et al 2008 ). Ideally, the cow adapts to this increased demand by increasing calcium absorption from the gastrointestinal tract and the mobilisation of calcium reserves from bone (Radostits et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Colostrum contains approximately four times more calcium than normal milk (Anderson et al 2007 ; Tsioulpas, Grandison & Lewis 2007 ). Such sudden drainage of large amounts of calcium into milk can overwhelm the cow’s homeostatic mechanisms (Rizzo et al 2008 ). Ideally, the cow adapts to this increased demand by increasing calcium absorption from the gastrointestinal tract and the mobilisation of calcium reserves from bone (Radostits et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that altered cerebrospinal fluid (CSF) or blood chemistry may cause motor dysfunction (ie: hypokalemia: (Ahlawat and Sachdev, 1999); high glycine: (Cui et al, 2005); hypermagnesemia: (Joo Suk, 2008); hypocalcemia: (Rizzo et al, 2008)). Previous work has determined that circulatory system opening was a viable insult to 2-3 dpf zebrafish embryos, and that these embryos survive for at least two days (Downes and Granato, 2006;Saint-Amant and Drapeau, 2000).…”
Section: 24: Opening the Circulatory System Rescues Paralysis And mentioning
confidence: 99%